The Emergence of Waqf Bank: A Social welfare Alternative in Indonesia - Gunawan Baharuddin; Bayu Taufiq Possumah (Media Syari'ah, 2017)
Rapid growth of Islamic Bank for the last decades shows a massive positive impact not only for the muslim itself but also for the non-muslim because the unique dan different offered system. Unfortunately, the Islamic banking industry nowadays only touches on a few minor aspects of the contribution to increase prosperity of the "small" peoples. However, 56.5 millions unit of Micro and Smal-Medium Enterprises (2012) has contributed 60% of Indonesian GDP and about 97% of labor force are become a strong reason for Indonesia to have better and stronger economy. Thus, waqf bank issue raises as a capital source to figure out this problem. This paper tries to explore further possibility development of waqf bank as one of alternatif solution to achieve social welfare and poverty alleviation.